Vocalizations as a conservation tool: an auditory survey of the Andean titi monkey Callicebus oenanthe Thomas, 1924 (Mammalia: Primates: Pitheciidae) at Tarangue, Northern Peru - Aldrich, Brooke Catherine; Molleson, Lucy; Nekaris, K.A.I (Contributions to zoology (Amsterdam, Netherlands : 1995), 2008)
Titi monkeys (Callicebus), morphologically cryptic primates, have been difficult to survey using traditional sighting-based line transect methods. Callicebus-species regularly engage in loud, ritualized singing bouts, which could allow for the use of alternate, potentially more accurate call-based survey methods to monitor populations. The Andean titi monkey, C. oenanthe, is endemic to a small region of northern Peru, an area subject to widespread and rapid deforestation and human colonization. We conducted a call-based survey of C. oenanthe at Tarangue, a 74 ha private reserve near Moyobamba. Triangulation of calls was used to map groups of titi monkeys on and around the reserve. 73 mapped calls were used to estimate the presence of between three and six groups per listening area - a total of 23 groups entirely or partially within the borders of Tarangue, yielding an estimated population density of 1.41 individuals per ha. Observations were much greater than those resulting from a visually-based survey conducted at Tarangue three years earlier. These higher estimates are probably not only due to this more suitable survey method; incessant destruction of habitat occurring in the area surrounding Tarangue may have caused the reserve to become a refuge for displaced individuals, with diminished opportunities for dispersal and establishment of new territories. Immediate measures to prevent further fragmentation within the Andean titi monkey’s geographic range are essential in order to allow the species to persist. We recommend the use of triangulation of calls for future surveys of titi monkeys.